The Anatomy of Political Money in Indonesia: Challenges to Electoral Integrity and Strategies for Restoring Substantive Democracy - Muhammad Agims (Anthroposia: Journal of Social and Human Development, 2026)
Political money remains one of the most persistent challenges confronting democratic development in Indonesia. This study examines the anatomy of political money, its consequences for electoral integrity and democratic governance, and potential strategies for restoring substantive democracy. The research employs a non empirical qualitative design using a descriptive and analytical literature approach based exclusively on secondary sources, including academic publications, legal documents, election monitoring reports, and institutional records. Data were analyzed through thematic categorization, comparative interpretation, and critical synthesis supported by source triangulation. The findings indicate that political money is sustained by structural weaknesses in political institutions, deficiencies in campaign finance governance, and limited accountability mechanisms. Its consequences include distorted electoral competition, declining political neutrality, weakened democratic accountability, increased corruption incentives, and the erosion of public trust in democratic institutions. The study further finds that the persistence of transactional politics contributes to democratic regression and compromises the realization of substantive democracy. Institutional reforms emphasizing campaign finance transparency, electoral justice, constitutional safeguards, and democratic accountability are essential for strengthening electoral integrity and promoting sustainable democratic governance in Indonesia.